Proof by Contradiction/Variant 3/Formulation 1

From ProofWiki
Jump to: navigation, search

Theorem

$p \implies \neg p \vdash \neg p$


Proof

By the tableau method of natural deduction:

$p \implies \neg p \vdash \neg p$
Line Pool Formula Rule Depends upon Notes
1 1 $p \implies \neg p$ Premise (None)
2 2 $p$ Assumption (None)
3 1, 2 $\neg p$ Modus Ponendo Ponens: $\implies \mathcal E$ 1, 2
4 1, 2 $\bot$ Principle of Non-Contradiction: $\neg \mathcal E$ 2, 3
5 1, 2 $\neg p$ Proof by Contradiction: $\neg \mathcal I$ 2 – 4 Assumption 2 has been discharged


$\blacksquare$


Sources